POLITIK HUKUM PENGATURAN PARTISIPASI PUBLIK DALAM PEMBENTUKAN UNDANG-UNDANG DI INDONESIA DARI MASA KE MASA - Nur Fathimah Azzahra Syafril; Fitriani Ahlan Sjarif (PALAR (Pakuan Law review), 2023)
AbstractThis article examines the legal politics of regulating public participation in the formation of laws in Indonesia over the time and its implementation. This research is a normative legal research, with library research data collection method. From the perspective of legal politics, normative arrangements regarding public participation in the formation of laws shows a positive progressivity where public participation in the formation of laws is regulated clearer and more comprehensive, especially from the meaning and what participation is to be achieved in the formation of laws. The meaning and participation to be achieved is meaningful participation achieved through fulfilling the right to be heard, the right to be considered, and the right to be explained. However, although normatively there is a progressivity in regulatory aspect, there are still problems at the implementation level. Among them is the promulgation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation which serves as the correction to Law Number 11 of 2020 concerning Job Creation is a wrong approach which actually ignores the importance of public participation in the formation of a law. Keywords: Public Participation, Legal Politics, Laws, Government Regulations in Lieu of Laws AbstrakArtikel ini mengkaji politik hukum pengaturan partisipasi publik dalam pembentukan undang-undang di Indonesia dari masa ke masa dan implementasinya. Penelitian ini merupakan penelitian hukum normatif, dengan metode pengumpulan data studi kepustakaan. Dari perspektif politik hukum, pengaturan normatif mengenai partisipasi publik dalam pembentukan undang-undang menunjukkan progresivitas dimana partisipasi publik dalam pembentukan undang-undang diatur semakin jelas dan komprehensif terutama dari makna dan partisipasi apa yang ingin dicapai dalam pembentukan undang-undang. Makna dan partisipasi yang ingin dicapai sesuai pesan Putusan Mahkamah Konstitusi yaitu meaningful participation yang diharapkan dapat memenuhi right to be heard, right to be considered, dan right to be explained terlihat telah di akomodir. Meskipun secara normatif terdapat peningkatan dalam pengaturan, namun sayangnya diundangkannya Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 tentang Cipta Kerja, yang  merupakan perbaikan dari UU Nomor 11 Tahun 2020 tentang Cipta Kerja justru mengabaikan pentingnya partisipasi publik dalam sebuah pembentukan undang-undang. Kata Kunci: Partisipasi Publik, Politik Hukum, Undang-Undan, Peraturan Pemerintah Pengganti Undang-Undang